Influence of Climate Change on Probability of Carbonation-Induced Corrosion Initiation - Hassan, Mostafa; Amleh, Lamya (Periodica Polytechnica Civil Engineering, 2024)
The consequences of climate change on infrastructure, particularly reinforced concrete (RC) bridges, have rapidly increased in recent years. These consequences are primarily driven by the surge in CO2 emissions, which significantly impacts the carbonation depth of RC structures. This study aims to investigate the probability of carbonation-induced corrosion initiation (PCICI) in RC bridge elements. To achieve this, the investigation incorporates a range of concrete covers, varying from 30 to 50 mm, and considers different concrete mixes with cement contents of 400, 350, and 250 kg/m3. The investigation utilizes the Monte-Carlo simulation method, considering different representative concentration pathways (RCPs) to account for two emission scenarios: RCP2.6 (low emission scenario) and RCP8.5 (high emission scenario). By analyzing projected CO2 concentrations and maximum temperature, the study provides insights into the potential corrosion initiation risks in RC bridges. The findings indicated a significant 66.3% increase in PCICI for a cement content of 250 kg/m3, compared to 400 kg/m3, under the RCP8.5 scenario, specifically when using a concrete cover of 30 mm by 2100. The study also revealed that the PCICI approached an approximate value of zero when concrete covers were set at 45 and 50 mm regardless of the variations in cement contents and the duration considered, for both the RCP2.6 and RCP8.5 scenarios.